2021
DOI: 10.1021/acs.inorgchem.1c02850
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Side-On V(III)-(η2-O2) through the Intermediacy of a Low-Valent V(II) in a Metal–Organic Framework

Abstract: We report the isolation of vanadium(II) in a metal− organic framework (MOF) by the reaction of the chloride-capped secondary building unit in the all-vanadium(III) V-MIL-101 (1) with 1,4-bis(trimethylsilyl)-2,3,5,6-tetramethyl-1,4-dihydropyrazine. The reduced material, 2, has a secondary building unit with the formal composition [V II V 2 III ], with each metal ion presenting one open coordination site. Subsequent reaction with O 2 yields a side-on η 2 vanadium-superoxo species, 3. The MOF featuring V(III)supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Recently, Dinca's group reported that the post-synthetic functionalization of reduced material V(II)-MIL-101 containing a mixed-valence [V II V 2 III ] unit with O 2 yields side-on vanadium (III)-superoxo species rather than V IV or V V species. 51 On this basis, we can conclude that some vanadium(III) species are O 2stable. Given that the syntheses of 1, 2 and 4 are remarkably insensitive to air, we have investigated their adsorptive properties of O 2 .…”
Section: Gas Adsorptionmentioning
confidence: 86%
“…Recently, Dinca's group reported that the post-synthetic functionalization of reduced material V(II)-MIL-101 containing a mixed-valence [V II V 2 III ] unit with O 2 yields side-on vanadium (III)-superoxo species rather than V IV or V V species. 51 On this basis, we can conclude that some vanadium(III) species are O 2stable. Given that the syntheses of 1, 2 and 4 are remarkably insensitive to air, we have investigated their adsorptive properties of O 2 .…”
Section: Gas Adsorptionmentioning
confidence: 86%
“…MOFs composed of low‐valent V II , [34] Ti III[35] and Cr II[36] nodes have received significant attention in recent years for their potential applications in catalysis [37] and gas adsorption/separation [34b] . A mixture of direct solvothermal synthesis [14b,35a,b,38] and post‐synthetic modification [34a,35c,37c] techniques have been employed to prepare these materials. For example, air‐sensitive Ti III precursors demand rigorous glove‐box techniques throughout synthesis and handling, [35a] motivating the development of alternative post‐synthetic methods.…”
Section: Direct Synthesis Of Mofs Featuring Low‐valent Metalsmentioning
confidence: 99%
“…For example, air‐sensitive Ti III precursors demand rigorous glove‐box techniques throughout synthesis and handling, [35a] motivating the development of alternative post‐synthetic methods. Frameworks featuring guest‐accessible or coordinatively unsaturated V II , Ti III or Cr II sites undergo redox chemistry with O 2 to form η 2 ‐V III ‐superoxo species, [34a] Ti IV peroxide/superoxide [34a] and superoxide Cr III species [38] which, in testament to the robustly crystalline MOF supports, have been structurally elucidated via X‐ray diffraction techniques [14b,38] . As such, V II sites have been identified as particularly promising adsorbents owing to strong π‐backbonding interactions between π‐acids and diffuse 3 d ‐orbitals of the electron‐rich V II centers, facilitating exceptional H 2 uptake, [34b] selective adsorption of N 2 over methane, and of olefins over paraffins [14b] .…”
Section: Direct Synthesis Of Mofs Featuring Low‐valent Metalsmentioning
confidence: 99%
“…Numerous biological and industrial processes rely on the unique ability of transition-metal centers to coordinate dioxygen gas (O 2 ) in a reversible manner. , In nature, the transport and storage of O 2 in aerobic organisms is performed by a handful of proteins with different metallocofactors, including hemoglobin/myoglobin (heme iron), hemocyanin (dicopper), , and hemerythrin (nonheme diiron). , The oxygenation of transition-metal centers generates an impressive variety of structural motifs in both biological and synthetic environments. Mononuclear sites typically coordinate O 2 to yield end-on (η 1 ) metal-superoxo species like the one observed in oxy-hemoglobin. , In other cases, the O 2 -derived ligand adopts a side-on (η 2 ) geometry, as observed in numerous coordination complexes and some O 2 -absorbing MOFs. , The deoxy forms of hemocyanin (Hc) , and hemerythrin (Hr) , possess dicopper­(I) and diiron­(II) sites, respectively, that reduce O 2 by two electrons to generate (hydro)­peroxo ligands. The peroxo ligand of oxy-Hc binds in a symmetric, side-on manner to yield a μ-η 2 :η 2 [Cu II 2 (O 2 )] core, whereas the hydroperoxo ligand of oxy-Hr adopts an end-on (η 1 ) [Fe III Fe III –OOH] geometry .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In other cases, the O 2 -derived ligand adopts a side-on (η 2 ) geometry, as observed in numerous coordination complexes 10−14 and some O 2 -absorbing MOFs. 15,16 The deoxy forms of hemocyanin (Hc) 4,5 and hemerythrin (Hr) 6,7 possess dicopper(I) and diiron(II) sites, respectively, that reduce O 2 by two electrons to generate (hydro)peroxo ligands. The peroxo ligand of oxy-Hc binds in a symmetric, side-on manner to yield a μ-η 2 :η 2 [Cu II 2 (O 2 )] core, 5 whereas the hydroperoxo ligand of oxy-Hr adopts an end-on (η 1 ) [Fe III Fe III −OOH] geometry.…”
Section: ■ Introductionmentioning
confidence: 99%